2015
DOI: 10.1038/nature14466
|View full text |Cite
|
Sign up to set email alerts
|

Recursive splicing in long vertebrate genes

Abstract: It is generally believed that splicing removes introns as single units from pre-mRNA transcripts. However, some long D. melanogaster introns contain a cryptic site, called a recursive splice site (RS-site), that enables a multi-step process of intron removal termed recursive splicing 1,2 . The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
285
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(297 citation statements)
references
References 31 publications
8
285
4
Order By: Relevance
“…In the second step, splicing from a 59 splice site either at the start of the cassette exon or downstream of it results in removal and inclusion of the cassette exon, respectively. Like SR30.3, most of the cassette exon variants resulting from recursive splicing in vertebrate genes are targeted by NMD (Sibley et al, 2015). Interestingly, the regulated intron in SR30 and the corresponding introns from other SR genes showing SR30-like AS patterns are exceptionally long, with 942 nucleotides for SR30 and ranging from 765 to 1100 nucleotides for the other cases (Supplemental Fig.…”
Section: Possible Alternative Routes For the Generation Of The Sr303mentioning
confidence: 99%
See 2 more Smart Citations
“…In the second step, splicing from a 59 splice site either at the start of the cassette exon or downstream of it results in removal and inclusion of the cassette exon, respectively. Like SR30.3, most of the cassette exon variants resulting from recursive splicing in vertebrate genes are targeted by NMD (Sibley et al, 2015). Interestingly, the regulated intron in SR30 and the corresponding introns from other SR genes showing SR30-like AS patterns are exceptionally long, with 942 nucleotides for SR30 and ranging from 765 to 1100 nucleotides for the other cases (Supplemental Fig.…”
Section: Possible Alternative Routes For the Generation Of The Sr303mentioning
confidence: 99%
“…Recently, further examples of recursive splicing events, involving generation of zero nucleotide exons, have been described for D. melanogaster (Duff et al, 2015). Identification of recursive splicing in vertebrate genes (Sibley et al, 2015) demonstrated that this mechanism is not restricted to D. melanogaster. Interestingly, all of the recursive splicing events found in human can result in cassette exon inclusion (CookAndersen and Wilkinson, 2015;Sibley et al, 2015), equivalent to the proposed consecutive splicing events resulting in SR30.3.…”
Section: Possible Alternative Routes For the Generation Of The Sr303mentioning
confidence: 99%
See 1 more Smart Citation
“…First, LITseq, unlike other intron probing approaches, can be adapted to define 3 ′ splice sites, by targeting the 3 ′ termini of excised but intact introns. By defining 5 ′ splice sites, branch sites, and 3 ′ splice sites, LIT-seq would not only allow the empirical annotation of introns but would also have the potential to reveal recursive splicing events, in which the spliceosome excises large introns by sequentially removing nested introns (Hatton et al 1998;Lopez and Séraphin 2000;Sibley et al 2015;Duff et al 2015). While the fully processed mRNA product cannot distinguish between intron excision in a single step from excision in multiple recursive steps, the intron products resulting from these two alternative pathways do distinguish between these mechanisms, because the lariats effectively record each splicing event.…”
Section: Future Applications Of Lit-seqmentioning
confidence: 99%
“…Duff et al 5 report that this recursive splicing process occurs in the fruit fly Drosophila melanogaster much more commonly than was previously thought. b, Sibley et al 6 find that some recursively spliced messenger RNAs -including all those known in humans -contain a recursive splicing (RS) exon. The RS exon can be either completely removed or retained in the mature mRNA, depending on which of two competing 5ʹ splice sites is used in the second step.…”
mentioning
confidence: 99%